2021
DOI: 10.1080/11038128.2021.1939414
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of weighted blankets on sleep and everyday activities – A retrospective follow-up study of children and adults with attention deficit hyperactivity disorder and/or autism spectrum disorder

Abstract: Kjellberg (2021): The effectiveness of weighted blankets on sleep and everyday activities -A retrospective follow-up study of children and adults with attention deficit hyperactivity disorder and/or autism spectrum disorder,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…The children in our study experienced improved sleeping patterns such as a shorter time before falling asleep, fewer awakenings, and less disturbance from the environment when using a weighted blanket. Weighted blankets may be an intervention that strengthens the cues of sleep onset by enhancing sensory stimuli in connection to sleep, lowering distraction from other stimuli, and improving the routine connected to preparing/going to sleep [ 17 , 30 ]. The weighted blankets can help the child to stay in bed, calming down and establish a routine that promotes sleep, and refrain from activating in other activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The children in our study experienced improved sleeping patterns such as a shorter time before falling asleep, fewer awakenings, and less disturbance from the environment when using a weighted blanket. Weighted blankets may be an intervention that strengthens the cues of sleep onset by enhancing sensory stimuli in connection to sleep, lowering distraction from other stimuli, and improving the routine connected to preparing/going to sleep [ 17 , 30 ]. The weighted blankets can help the child to stay in bed, calming down and establish a routine that promotes sleep, and refrain from activating in other activities.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the complexity of sleep and sleep routines confirming the importance of looking beyond sleep duration [ 62 ] and taking a 24-hour perspective when it comes to sleep interventions in children with ADHD. In order to improve routines connected to sleep, the benefits of using weighted blankets may be augmented by combining them with standard sleep hygiene recommendations, which are proposed as constituting part of the first-line treatment for children with ADHD [ 5 , 17 , 63 , 64 ]. This is common practice in the prescription process of weighted blankets [ 19 ] and will ensure that individual needs are met from evening to morning routines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ongoing disruptions in sleep and rest could impact on people’s choice, performance, and participation in variety of occupations, i.e., one’s occupational balance (Dhas & Wagman, 2020; Ho, Dür, Stamm, & Siu, 2020). Reviews (e.g., Ho & Siu, 2018; Smallfield & Molitor, 2018) showed that the range of occupational therapy interventions for sleep problems include sleep hygiene education, cognitive-behavioural therapy for insomnia (CBT-i) (Eakman et al, 2017), prescription of sleeping aids (e.g., quilt, Dreampad pillow or weighted blankets) (Bolic Baric et al, 2021), physical activities, mind-body activities and mindfulness training, and lifestyle interventions (Leland et al, 2016). While there is a growing interest to develop sleep intervention programme in occupational therapy, these reviews showed that many programmes were not designed or organised based on occupational therapy theories (Ho & Siu, 2018).…”
Section: Introductionmentioning
confidence: 99%